Implementasi Inovasi Smart Cane Berbasis Smartphone Pada Tunanetra - M Febriyanto Firman Wijaya; Radius Setiyawan; Dede Nasrullah; Lukman Hakim; Syarifuddin Syarifuddin; Firman Firman; Nur Hidayatullah Romadhon; M Taufiqur Rahman (Journal of Community Development, 2025)
Blind people are one of the disabled groups who have limited vision, who require the help of other people or certain tools to carry out daily activities. So far, the blind has used canes to help them when walking, but the canes they usually use are not helpful enough. For this reason, it is necessary to implement an innovative smart cane with smartphone-based sensors for the blind. The implementation method was to carry out empowerment with a participatory approach, by implementing the smart cane innovation tool for the blind. The smart cane was equipped with sensors, light reflectors, GPS (Global Positioning System) navigation and an emergency button. The sensor functions to helps identify surrounding objects, making it easier for the blind to walk without worrying about tripping or being blocked by objects while walking. Light reflectors provide additional security by reflecting light when walking at night. The implementation of the smart cane was very helpful and made it easier for the blind to make their activities safer and more comfortable. Smart cane one of the innovative solutions that need to continue to be developed to help disabled groups, especially the blind, so that they have equal access to other people.